Compact wooden roofs with smart vapour barrier – Pilot project experiences - Bunkholt, Nora Schjøth; Gullbrekken, Lars; Geving, Stig; Kvande, Tore (E3S Web of Conferences, 2020)
Compact roofs are normally built without organic materials between the vapour barrier and the roof membrane due to moisture safety risks. However, laboratory measurements indicate that organic materials could be used provided that a smart vapour barrier (SVB) is applied at the warm face of the roof construction. The aim of this study is to investigate the moisture and temperature conditions in three fullscale flat compact wooden roofs with SVB. The roofs are part of two pilot projects located in Longyearbyen, Svalbard and Malvik, Norway. The paper presents the two projects including the premises for construction of the roofs and provides preliminary measurement results. The roofs are instrumented to measure moisture content and temperature in the wooden roof beams. The initial results from Longyearbyen show that the moisture content in the wooden beams is low and indicate that compact wooden roofs with SVB may be a solution with acceptable moisture risk in the arctic climate. The initial results from Malvik show that there might be a risk of mould growth in the roof as the built-in moisture in the wooden beams was up to 24 weight-%. In both projects, the moisture content in the beams in general was higher close to the roof underlay than close to the SVB. publishedVersion © The Authors, published by EDP Sciences. This is an open access article distributed under the terms of the Creative Commons Attribution License 4.0 (http://creativecommons.org/licenses/by/4.0/).